Introduction to self-healing concrete via biological process / Amalinda Othman - Othman, Amalinda (2018)
Concrete is the most important material used in order to construct a building. Malaysia receives extreme variations in rainfall. Due to the rainfall average, water may enter into the cracks occurred in a building. The repairing process of concrete may take some time and the cracks affect the surrounding especially reinforced concrete at a bridge. One of the effective ways to overcome the problem is by applying self-healing concrete that has been used by other countries. The objectives of the research are to understand the concept of self-healing concrete using biological process, to identify the practise of new self-healing concrete process in another country and to propose the concept of biological selfhealing concrete that can be adapted to the building in Malaysia. In order to achieve the objectives, the method used to conduct this research is desk study on the relevant topics related to the self-healing concrete in locally and abroad. Therefore, the critical review will become the basis of a new concept for self-healing concrete by biological process to suit local condition. From the review, it was found that mixing the concrete with limestone-producing bacteria may repair any cracks that formed in the concrete.